An HIV/AIDS intervention programme to change knowledge, attitudes, and behaviour of members of the South African Police Service - Maphoso, Lesiba Samuel (My University, 2008)
The purpose of this study was to investigate if there is any change in the HIV/AIDS knowledge, attitude, and behaviour of the South African Police Service’s (SAPS) employees after attending the HIV/AIDS intervention programme. One hundred and eight employees who attended the HIV/AIDS awareness workshop participated as experimental group (n=51) while those who attended the suicide prevention and disability workshop participated as control group (n=57). Pre-tests were administered before the workshops to all participants while the post-tests were administered after the workshops. The results were analysed using 2(Group: Experimental versus Control Group) x 2(Time: Pre-test versus Post-test, a repeated measure) Analyses of Variances (ANOVA). The research findings showed that there was a significant change in HIV/AIDS knowledge after employees have attended the HIV/AIDS awareness workshop. Results also indicated that there was a significant mean score difference in HIV/AIDS knowledge among the rank groups (Administration, Junior, and senior) with administration and junior employees having more HIV/AIDS knowledge than senior employees. There was also a significant mean score difference in HIV/AIDS attitude among ranks with employees in the senior ranks having less positive attitudes than the employees in the administration and junior ranks. There was a significant interaction between the ranks and the time of testing because those in higher ranks had higher gains in knowledge than those in lower ranks. vi In terms of HIV/AIDS knowledge among age groups, the study revealed that there was a significant main effect of age group (22-33, 34-43, 44 and over years) with older people having less HIV/AIDS knowledge than younger employees. There was also a significant main effect of age group and attitude, with employees of 44 years and over having less favourable HIV/AIDS attitudes than employees in the 22-33 and 34-43 years groups. The study also suggested that further study should look in the problems encountered at implementing the HIV/AIDS intervention programmes and also at what is causing the gap in HIV/AIDS knowledge and attitude among age and rank groups.
Thesis (M.ED.) --University of Limpopo, 2008.
Keywords: Attitudes